Performance study of a hybrid photovoltaic/thermal system (Research, Society and Development, 2021)
This work presents a performance study of a hybrid photovoltaic/thermal system (PVT), comparing it with a traditional photovoltaic system (PV). The electrical and thermal power, efficiency and energy produced by the systems were analyzed. The photovoltaic module (PV) used was the MSX 77 of the SOLAREX brand, composed of polycrystalline solar cells, whose peak power is 77 Watts. The PVT system analyzed was of the type PVT-liquid, composed of the same PV module and a flat solar collector of the plate type, the water supply of the collector was of the type forced by gravity. In order to determine the characteristic curves of the PV module and, consequently, the maximum electrical power generated, a load bank formed by power resistors was developed. The thermal power was quantified by measuring the water flow that fed the collector and the temperature difference of the inlet and outlet water. With the powers and solar radiation incident on the systems, the efficiencies were determined. The PVT system reduced the temperature of the PV module, increasing the efficiency of electrical generation, providing an increase in the order of 6.9% in the average daily electrical energy. The PVT system, in addition to providing an increase in electrical energy, also provides thermal energy with a higher efficiency than electrical. The heated water can be used to feed water heating systems for bathing, helping to reduce the consumption of electricity in a home.